Design of Enterprise Information System Architecture with Oracle Architecture Development Process (OADP) Case Study in Vocational High Schools - Muhammad Prakarsa Al Qadr Saleh; Sofia Dewi (International Journal of Quantitative Research and Modeling, 2020)
The development of information and communication technology has led to increasingly competitive competition among organizations. The management of the organization is required to build and develop a fast, precise and accurate information system (IS) to assist business activities in achieving organizational goals and providing services to stakeholders, especially in relation to data, information, technology and applications. ORACLE Architecture Development Process (OADP) is a method or frame of reference for building an information architecture oriented to business needs. This consists of the data architecture, applications, technology and implementation plans of the architectures that have been created to support business activities in achieving the organization mission. The OADP describes the data architecture, applications and technology required to support the organization business. Vocational High Schools cannot be separated from the needs of business and information architecture. A lot of information is generated from all processes that occur in the Vocational High School environment every day but the existing data management is not efficient because it has not been thoroughly connected. This may take a long time to process past data or calculate future needs because the data management process is still running separately. Because of these cases, the modeling information architecture in an organizational environment is required as a stage in supporting the running of business processes in the organization.